2001
DOI: 10.1021/la010646k
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Spin−Echo Study of Dynamics of Hydrophobically Modified Polymer-Doped Surfactant Bilayers

Abstract: We characterize the effect of adsorbed hydrophobically modified polymers (hm-polymers) on the dynamics of surfactant bilayers by small-angle neutron scattering and neutron spin-echo spectroscopy. Two kinds of hm-polymers, (a) hydrophobically modified poly(acrylate) with tetradecyl (C14) sidegroups randomly grafted to the poly(acrylate) backbone and (b) poly(PEG6k-lysine-stearylamide) with equally spaced hydrophobes, are added to bilayers of penta(ethylene glycol) dodecyl ether (C12E5) and hexanol. Both bare an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Influence of the grafted polymers on the elastic properties has been carefully investigated by some researchers. [25][26][27]30,34,41,42,[46][47][48][49] It is known that grafting polymers enhances the bending modulus and the repulsive interaction between membranes. Castro-Roman et al explained the enhancement of the repulsive Helfrich interaction by renormalizing the thickness of polymer layer into an effective thickness of membranes.…”
Section: Development Of the Oily Streak Networkmentioning
confidence: 99%
“…Influence of the grafted polymers on the elastic properties has been carefully investigated by some researchers. [25][26][27]30,34,41,42,[46][47][48][49] It is known that grafting polymers enhances the bending modulus and the repulsive interaction between membranes. Castro-Roman et al explained the enhancement of the repulsive Helfrich interaction by renormalizing the thickness of polymer layer into an effective thickness of membranes.…”
Section: Development Of the Oily Streak Networkmentioning
confidence: 99%
“…A particularly interesting parameter for the understanding of the bilayer elasticity is its thickness, and there are some studies investigating its influence [27][28][29][30][31] on the membrane rigidity. A study on bilayer vesicles assembled from amphiphilic diblock copolymers showed that the mean bending rigidity κ for large polymersomes scales with the hydrophobic membrane thickness to the power two.…”
Section: Introductionmentioning
confidence: 99%
“…hydrophobically modied polymers like PAA or PEG; 4,[11][12][13][14] amphiphilic poly(ethylene propylene)-poly(ethylene oxide) added to bicontinuous microemulsions; 10,15,16 and a triblock-peptide added to a lamellar phase.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the case of microemulsions neutron spin-echo (NSE) spectroscopy was found to be a useful tool to study the elastic moduli of such interfacial lms. 1,2 In this context layered structures formed by amphiphilic block copolymers and surfactants also received much attention in recent years [3][4][5] as polymer-lipid interactions play a key role in biological membranes and as mixtures of amphiphilic polymers and surfactants are found in a growing number of technical products. 6 The dynamic properties of these membranes are of particular interest and can be studied by NSE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation